The Efficacy of Oxytocin Massage on Lactation in Nursing Mothers within the Cidahu Health Center's Jurisdiction, Kuningan Regency - Purnamasari, Lina; Tonasih, Tonasih; Suminar, Erni Ratna (Ann Publisher, 2024)
Background. Breast milk is the ideal food for neonates and serves as the exclusive nutritional source needed by infants during the first months of life. Oxytocin massage is a technique employed to mitigate insufficient breast milk production. Aim. This study aims to investigate and assess the effect of oxytocin massage on increasing breast milk production in nursing women. Methods. This study used a descriptive experimental design featuring pre- and post-test evaluations to determine the effect of oxytocin massage on breast milk supply in nursing mothers. The research will be place at the Cidahu Health Center in Kuningan Regency, West Java Province. The event is planned for June to July 2024, featuring 18 postpartum ladies. Research Results: A majority of responders, comprising 14 persons (77.8%), are aged between 20 and 35 years. A substantial segment, consisting of eight persons (44.4%), has advanced degrees. Furthermore, 11 respondents (61.1%) possess multipara parity, whilst six individuals (33.3%) are employed in the informal sector. The Wilcoxon test produced a significance value of 0.000, which is below 0.05, signifying a substantial alteration in breast milk production pre- and post-oxytocin massage. The credible hypothesis posits that Ha is accepted while Ho is rejected. Conclusion: The predominant demographic of respondents was those aged 20 to 35 years, possessing a collegiate education, exhibiting multipara parity, and engaged in homemaking. A association was observed between oxytocin massage and lactation in postpartum mothers at the Cidahu Health Center in Kuningan Regency, with a significance level of p-value 0.000. Implication: Health workers can provide knowledge related to Oxytocin Massage to the community through counseling and other interesting content and can apply Oxytocin Massage to postpartum mothers.